Legal Politics Of State Assets Recovery By In Absentia Court In Act Number 20 Year 2001 Concerning Eradication Against Corruption - Titin Nurfatlah; Gina Meilinda; Fifi Rosalina; Usnadi Usnadi (Faculty of Law, University of Mataram, 2019)
State assets recovery is an important part of the law enforcement on corruption crimes. Therefore state assets recovery shall be state’s legal politics. This study intended to find out the Indonesian legal politics of state asset recovery through in absentia court. Method of this study is normative reseach and used statute approach and conceptual approach. Based on the analysis can be concluded that in absentia court have enumerated in Indonesian Law Regarding Eradicating Against Corruption. This is in line with the legal politics in the decree Of Indonesian People’s Consultative Assembly which emphasizes the acceleration of legal processes in criminal acts of corruption.